Pengelolaan Sampah Terpadu Berbasis Komunitas untuk Mendukung SDG 11: Kota dan Komunitas Berkelanjutan di Negara Bagian Trengganu, Darul Iman, Malaysia - Zubaidah, Evi; Mardhatillah, Annisa; Bin Ibrahim, Mohamad Asmawi; Dynda,; Pitriani, (BERDAYA : Jurnal Pengabdian Kepada Masyarakat, 2025)
Effective waste management is key to achieving sustainable cities and communities in line with SDG 11. In Trengganu State, Darul Iman, Malaysia, a community-based approach to waste management is implemented through active community participation in waste segregation, reduction, and recycling. The program involves educational campaigns, waste management training, and collaboration with local governments and NGOs. However, the program faces challenges such as low participation from some community members, limited infrastructure, and insufficient government support. To achieve sustainability, there is a need to enhance community education, develop waste management facilities, and strengthen collaboration between the government, the community, and the private sector. This community-based waste management approach is expected to serve as a replicable model in other regions to support SDG 11 and create cleaner, healthier environments.. Keywords: Community-based waste management, SDG 11, Trengganu Malaysia